2011
DOI: 10.1093/nar/gkr025
|View full text |Cite
|
Sign up to set email alerts
|

Mapping interactions between the RNA chaperone FinO and its RNA targets

Abstract: Bacterial conjugation is regulated by two-component repression comprising the antisense RNA FinP, and its protein co-factor FinO. FinO mediates base-pairing of FinP to the 5′-untranslated region (UTR) of traJ mRNA, which leads to translational inhibition of the transcriptional activator TraJ and subsequent down regulation of conjugation genes. Yet, little is known about how FinO binds to its RNA targets or how this interaction facilitates FinP and traJ mRNA pairing. Here, we use solution methods to determine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 49 publications
3
64
0
Order By: Relevance
“…RNA cross linking experiments have previously shown the residue corresponding to R58 as being implicated in RNA binding by FinO. Other residues implicated in RNA binding from this study of FinO clustered toward the N-and C-terminal helical extensions of this protein (Ghetu et al 2002;Arthur et al 2011).…”
Section: Discussionmentioning
confidence: 53%
“…RNA cross linking experiments have previously shown the residue corresponding to R58 as being implicated in RNA binding by FinO. Other residues implicated in RNA binding from this study of FinO clustered toward the N-and C-terminal helical extensions of this protein (Ghetu et al 2002;Arthur et al 2011).…”
Section: Discussionmentioning
confidence: 53%
“…). One early study showed that the 3′‐U 4 tail of FinP stem loop II was necessary for its efficient binding to FinO (Jerome and Frost, ), and later work showed that FinO protected lower parts of the stems and the 3′ single‐stranded regions of FinP (Arthur et al ., ). These observations are consistent with the better binding of L. pneumophila RocC protein to the 3′‐terminal stem loop of RocR sRNA with an adjacent U 3 CU tail than to a fragment composed of stem loops 1 and 2 devoid of the 3′ terminal extension (Attaiech et al ., ).…”
Section: Rnas Bound By Fino‐domain Proteinsmentioning
confidence: 97%
“…Horizontal gene transfer, especially conjugative transfer of plasmids that carry resistance genes, is the primary cause of bacterial antibiotic resistance and—on the larger scale—bacterial evolution (Zatyka and Thomas, 1998; Arthur et al, 2011). The self-transmissible plasmids, such as the well-studied fertility F-plasmids and IncP plasmid RP4 (also known as RK2), generally present a mobilization (MOB) region which includes the origin of transfer (oriT) and the relaxase gene.…”
Section: Introductionmentioning
confidence: 99%